2016
DOI: 10.1111/corg.12157
|View full text |Cite
|
Sign up to set email alerts
|

How Does Regulation Affect the Relation Between Family Control and Reported Cash Flows? Comparative Evidence from India and the United States

Abstract: Manuscript Type Empirical. Research Question/Issue We conduct a two‐country study to understand (i) how family and non‐family firms engage in classification shifting to manage reported operating cash flows in each country; (ii) how this behavior varies between the two countries; and (iii) how corporate governance regulation introduced independently in each country moderates the observed behavior. Research Findings/Insights We find that family ownership has different effects on quality of cash flow reporting in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 77 publications
1
10
0
Order By: Relevance
“…Consequently, Indian firms are likely to engage in cash flow manipulation. However, the magnitude of such misclassification is lower in India as compared to that in the USA (Nagar and Sen, 2016).…”
Section: Prior Literature and Hypothesis Developmentmentioning
confidence: 97%
“…Consequently, Indian firms are likely to engage in cash flow manipulation. However, the magnitude of such misclassification is lower in India as compared to that in the USA (Nagar and Sen, 2016).…”
Section: Prior Literature and Hypothesis Developmentmentioning
confidence: 97%
“…It is also shown that these institutional variations accordingly play a critical role in explaining cross‐national differences in corporate governance mechanisms (Adams, Licht, & Sagiv, ; Hooghiemstra, Hermes, & Emanuels, ; La Porta, Lopez‐de‐Silanes, & Shleifer, ; La Porta, Lopez‐de‐Silanes, Shleifer, & Vishny, ). For instance, a recent stream of research has addressed corporate governance in emerging economies such as China and India, whose institutional environments are less developed or quite different from those of advanced economies (Chen, Liu, & Lin, ; Huyghebaert & Wang, ; Lattemann, Fetscherin, Alon, Li, & Schneider, ; Li, ; Nagar & Sen, ; Singh & Gaur, ; Zhang, Chen, & Feng, ; Zhang, Gao, Guan, & Jiang, ). It is claimed that business groups are an organizational form that can overcome market imperfections prevalent in emerging economies (Colpan, Hikino, & Lincoln, ; They exhibit unique governance challenges as well as attributes to overcome broader strategic issues such as institutional voids or competitiveness, as summarized by Colli and Colpan's () article in this special issue.…”
Section: Introductionmentioning
confidence: 99%
“…Third, as described previously, a growing stream of literature documents that firms inflate reported CFO when they have incentives to do so (e.g., Gordon et al., 2017; Lee, 2012; Nagar & Sen, 2016). Collectively, this line of research suggests that firms manage CFO upward in response to incentives.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 88%
“…(2017) extend findings of Lee (2012) by showing that European firms with similar incentives are more likely to make classification choices to enhance reported CFO. Comparing the levels of CFO management between US and Indian firms, Nagar and Sen (2016) find that the magnitude of CFO management is higher for firms in India, which they characterize as having weaker corporate governance and investor protection, as compared to those in the United States.…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%